2014
DOI: 10.4236/cm.2014.54028
|View full text |Cite
|
Sign up to set email alerts
|

Microsatellite Analysis of <i>Panax ginseng</i> Natural Populations in Russia

Abstract: Panax ginseng C.A. Meyer is an endangered species in Russia. To restore this species, effective protective measures, including the reintroduction into favorable habitats, must be worked out considering the specificity of genetic structure of ginseng populations. One hundred and thirtynine P. ginseng plants were collected from the forests of nine administrative areas of Primorsky Territory of Russia and transferred to a collection nursery for further investigation. Microsatellite markers were used to study the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
23
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(29 citation statements)
references
References 35 publications
5
23
1
Order By: Relevance
“…It describes the proportion of heterozygosis expected under the Hardy-Weinberg (HW) equilibrium [47]. Previous studies have confirmed the excess heterozygosity in their ginseng populations [7,12,28,48]. Indeed, the present study also showed excess heterozygosity in these ginseng accessions ( Table 1).…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…It describes the proportion of heterozygosis expected under the Hardy-Weinberg (HW) equilibrium [47]. Previous studies have confirmed the excess heterozygosity in their ginseng populations [7,12,28,48]. Indeed, the present study also showed excess heterozygosity in these ginseng accessions ( Table 1).…”
Section: Discussionsupporting
confidence: 82%
“…Results of the present study showed a similar number of alleles (56) and average number of alleles (3.29) to results of Choi et al [28] (number of alleles = 51; average number of alleles = 3.0), while genetic diversity (0.490) in the present study was higher than (0.398) in the previous study. Reunova et al [12] have reported similar results (average number of alleles: 2.49; expected heterozygosity (He): 0.453) in 139 individual ginseng plants using 11 SSR primers. Otherwise, Bang et al [7] have reported a higher average number of alleles (4.3) and He (0.627) in 17 ginseng accessions using 8 SSR markers.…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…Whole genome data have also been used to design microsatellites for species identification, but these have found limited application [18, 4852]. Extensive population genetic studies have been done only on P. quinquefolius [5359] and P. ginseng [60, 61] due to their major economic importance.…”
Section: Evolution and Phylogenetics Of Panaxmentioning
confidence: 99%
“…In this regard, as codominant markers with high mutation rates (Jarne and Lagoda, 1996), nuclear microsatellites might provide novel insights into the polyploidy of Panax and domestication of P. ginseng . In previous studies, other microsatellites have been developed (Kim et al, 2007; Yang et al, 2008; Ahn et al, 2009; Van Dan et al, 2010; Choi et al, 2011; Reunova et al, 2014). Nevertheless, most of these studies developed microsatellites based on traditional Sanger sequencing, and the transferability of most of these microsatellites to congeneric species remains unknown.…”
mentioning
confidence: 99%